Conversational hypnosis versus standard of care to reduce anxiety in patients undergoing marker placement under radiographic control prior to breast cancer surgery: A randomized, multicenter trial - Lemoine, Lydie; Adam, Virginie; Galus, Xavier; Siles, Pascale; Coulon, Agnès; Grenier-Desforges, Jeannette; Orabona, Joseph; Kergastel, Isabelle; Wagner, Pierre; Salleron, Julia; Tosti, Priscillia; Huin-Schohn, Cécile; et al. (Frontiers in Psychology, 2022)
Background: Surgery is a cornerstone of breast cancer management. Prior to surgery, a wire marker is placed at the site of the tumour, to enable the surgeon to accurately localize the lesion during later surgery. This procedure can generate considerable anxiety for many patients. We investigated the value of conversational hypnosis (CH) in reducing anxiety in patients undergoing preoperative wire placement under radiographic control. Methods: Randomized, multicentre study in 7 centres in France. Inclusion criteria were patients aged >18 years with an Eastern Cooperative Oncology Group performance status ≤2, scheduled to undergo preoperative wire placement in one or several breast lesions. Patients were randomized in a 1:1 ratio, stratified by centre to undergo preoperative wire placement with or without the use of CH by a radiological technician trained in the CH technique. The primary endpoint was the percentage of patients with an anxiety score ≥6 on a visual analog scale ranging from 0 (absence of anxiety) to 10 (maximal anxiety). Secondary endpoints were pain score, perceived duration reported by the patient, technician satisfaction with their relationship with the patient, and ease of marker insertion reported by the radiologist. Semi-structured interviews were performed with patients to assess their perception of the marker placement procedure. Results: The trial was prematurely interrupted for futility after a planned interim analysis after accrual of 167 patients, i.e. half the planned sample size. Prior to marker placement, 29.3% (n=24) of patients in the control group had an anxiety score ≥6, versus 42.3% (n=33) in the CH group (p=0.08). After marker placement, the change of anxiety score was not significantly different between groups (11.0% (n=9) versus 14.3% (n=11), p=0.615). There was no significant difference in any of the secondary endpoints. In the interviews, patients from both groups frequently spoke of a feeling of trust. Conclusion: This study failed to show a benefit of conversational hypnosis on anxiety in patients undergoing marker placement prior to surgery for breast cancer. The fact that some caregivers had learned this personalized therapeutic communication technique may have had a positive impact on the whole caregiving team